2007
DOI: 10.1029/2007gl031823
|View full text |Cite
|
Sign up to set email alerts
|

Scaling relationships and evolution of distributary networks on wave‐influenced deltas

Abstract: [1] No genetic model can explain the variability in distributary network pattern on modern deltas. Here we derive scaling relationships for two processes known to create distributary channels and, with these laws, construct a simple model for distributary network evolution. The first process is mouth-bar deposition at the shoreline and subsequent channel bifurcation; the second is avulsionthe wholesale abandonment of a channel in favor of a new path. The former creates relatively small networks with power-law … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
190
1

Year Published

2009
2009
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(200 citation statements)
references
References 30 publications
9
190
1
Order By: Relevance
“…The fact that T s is much larger than these fluctuations and is associated with T ch , which characterizes an ''avulsion'' time scale, supports the idea of additional surface instabilities [Jerolmack and Swenson, 2007]. For example, on relatively short time scales in-channel instabilities force flow spreading and the formation of multiple bifurcation-based channels [Edmonds and Slingerland, 2007], and on longer time scales (e.g., T ch , T s ) another instability arises from differential topography, causing larger-scale shifts in the flow [Jerolmack and Mohrig, 2007;Jerolmack and Swenson, 2007]. The implication for distributary lobes in DB07 is that the site of lobe evolution may be established by fan topography, whereas the details of lobe growth are accomplished by a subset network of bifurcation channels that stem from a parent channel.…”
Section: Implication Of T S For Shoreline Dynamicssupporting
confidence: 49%
“…The fact that T s is much larger than these fluctuations and is associated with T ch , which characterizes an ''avulsion'' time scale, supports the idea of additional surface instabilities [Jerolmack and Swenson, 2007]. For example, on relatively short time scales in-channel instabilities force flow spreading and the formation of multiple bifurcation-based channels [Edmonds and Slingerland, 2007], and on longer time scales (e.g., T ch , T s ) another instability arises from differential topography, causing larger-scale shifts in the flow [Jerolmack and Mohrig, 2007;Jerolmack and Swenson, 2007]. The implication for distributary lobes in DB07 is that the site of lobe evolution may be established by fan topography, whereas the details of lobe growth are accomplished by a subset network of bifurcation channels that stem from a parent channel.…”
Section: Implication Of T S For Shoreline Dynamicssupporting
confidence: 49%
“…For the deltas we studied, static box counting of shoreline snapshots gives D = 1.03 ± 0.04, suggesting that shorelines of growing deltas are not fractal (since mathematically D > 1 corresponds to an "infinitely rough" fractal curve, while D = 1 corresponds to a "smooth" curve with only finite roughness [Mandelbrot, 1967;Turcotte, 1997]). Combined with previous observations on the non-fractality of beach coasts [Murray and Barton, 2007], where wave-driven alongshore transport is a significant process [Jerolmack and Swenson, 2007], this suggests that constructional coasts made of mobile sediment may be generally nonfractal. We note that allometric growth and a fractal boundary are conceptually distinct, i.e., isometric growth of a fractal curve should be possible in principle (although if measured with a fixed ruler size, isotropic expansion of a fractal would still yield allometric length-area scaling).…”
Section: Land Growthmentioning
confidence: 80%
“…In degrading deltas, enhanced compaction in organic-rich overbank areas [Törnqvist et al, 2008] may result in more fractal shorelines as non-channel areas subside below sea level, while in wave-dominated deltas diffusive dampening of the channelbifurcation instability [Jerolmack and Swenson, 2007] could result in non-fractal channel patterns.…”
Section: Discussionmentioning
confidence: 99%
“…Studies based on the relationship between the distributary network of wave-influenced deltas showed that wave energy controls the network topology by suppressing mouth-bar development, thereby preferentially eliminating smaller-scale distributaries [Jerolmack and Swenson, 2007].…”
Section: Introductionmentioning
confidence: 99%